A Hospital-Based Cross-Sectional Study on Hand Eczema in a Tertiary Care Centre of Western Nepal - Bikram Gyawali; Prabodh Regmi (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Hand eczema is a prevalent dermatological condition that often presents with inflammatory, pruritic, and occasionally painful lesions, significantly affecting patients’ quality of life and daily functioning. The study aimed to find out the demographical profile (age, sex, ethnicity) and the affected site, size and morphological features of the hand eczema in tertiary care hospital, western part of Nepal. Material and Methods: This was a hospital based descriptive cross-sectional study carried out after ethical approval from Internal Review Committee, DMCRI. The period of study was from 15 May, 2023 to last of April, 2024. Total 218 cases were included in the study. The data were analyzed using SPSS version 16. Chi-square test was performed to find out the relation of morphological features at 95% confidence interval. Results: The prevalence of hand eczema, who presented in DMCRI was 5%. Out of total 218 cases, the most commonly affected age group was 20 to 49 years, female to male ratio was 131:87(1.5:1). Chronic hand eczema cases were 185(85%), bilateral 191(87.5%). In our cases, dry palmar eczema was the most common morphology 68 (31.2%), followed by patchy vesicosquamous eczema 57 (26.1%). Conclusion: In our study the hand eczema prevalence was 5.3%. The females of middle age group were most commonly affected. The chronicity, bilateral involvement were the most commonly observed parameters. We observed the dry palmar eczema was the most commonly observed morphological feature followed by the vesicosquamous eczema.